Influence of Hospital Bed Count on the Positioning of Cardiovascular Interventional Radiology (IR) Nurses: Online Questionnaire Survey of Japanese IR-Specialized Radiological Technologists - Tomoko Kuriyama; Takashi Moritake; Go Hitomi; Koichi Nakagami; Koichi Morota; Satoru Matsuzaki; Hajime Sakamoto; Kazuma Matsumoto; Mamoru Kato; Hiroko Kitamura (Nursing Reports)
Background/Objectives: Interventional radiology (IR) utilizing X-rays can lead to occupational radiation exposure, posing health risks for medical personnel in the field. We previously conducted a survey on the occupational radiation exposure of IR nurses in three designated emergency hospitals in Japan. Our findings indicated that a hospital with 214 beds showed a higher lens-equivalent dose than hospitals with 678 and 1182 beds because the distance between the X-ray irradiation field and the IR nurse’s position of the hospital with 214 beds was shorter than those of 678 and 1182 beds. Based on these observations, we hypothesized that the number of hospital beds affects the distance between the X-ray irradiation field and the IR nurse’s position. Methods: To verify this hypothesis, we conducted a more extensive online questionnaire survey, focusing exclusively on hospitals that perform cardiovascular IR. Results: We analyzed data from 78 facilities. The results of this study confirmed our earlier findings, showing that both the number of physicians performing IR procedures and the distance from the X-ray irradiation field to the IR nurse’s position are influenced by the number of hospital beds. Additionally, factors such as the type of hospital, emergency medical system, annual number of IR sessions, location of medical equipment, and the positioning of IR nurses appear to be associated with the number of hospital beds. Conclusions: Understanding these relationships could enable the development of individualized and prioritized radiation exposure reduction measures for IR nurses in high-risk settings, provided that comprehensive occupational radiation risk assessments for cardiovascular IR consider the number of hospital beds and related factors. This study was not registered.